Reflections, Thoughts, And Concerns for The Future of Adult Education - Edgar J. Boone (Adult Education Research Conference, 2009)
I begin my remarks by reminding you that I am one of you. My journey as an Adult Educator spans a period of almost 60 years beginning as a County 4‐H and Youth Development Agent in the Louisiana Cooperative Extension Service and extending to my retirement as the William Dallas Distinguished Professor of Adult and Community College Education and Director of the Academy for Community College Leadership, Advancement, Modeling, and Innovation (ACCLAIM) at North Carolina State University and the past 10 years of my retirement.